A Clinical Study on the Pattern of Mitral Valvular Disease in a Peripheral Tertiary Hospital in Bangladesh (Cardiovascular Journal, 2010)
Background: Rheumatic mitral valvular disease (MVD) is a common cause of cardiovascular morbidity and mortality in Bangladesh. Many patients are diagnosed late, get maltreated, and develop complications, which can be minimized if early diagnosis could be made. Objectives: The study was carried out to determine the common symptoms and signs of mitral valvular disease in our population, to find out the incidence and pattern of complications, to list the pattern of valve lesions, to identify the common findings in different investigations and to find out the causes of delay in diagnosis. Methods: Fifty consecutive cases of isolated MVD of rheumatic origin admitted in Rajshahi Medical College Hospital, Rajshahi, Bangladesh, from July, 2002 to March, 2003 were included. Detailed history was taken, and clinical examination was performed. Chest skiagram, 12-lead ECG and echocardiography were performed in all patients. Other investigations include complete blood counts, anti-streptolysin O (ASO) titre, C-reactive protein (CRP), blood sugar, serum creatinine and routine urinalysis. Results: The peak incidence of MVD was found in the third decade (34%), 14 (28%) patients were